2014
DOI: 10.1039/c3mb70181f
|View full text |Cite
|
Sign up to set email alerts
|

Application of molecular docking and ONIOM methods for the description of interactions between anti-quorum sensing active (AHL) analogues and the Pseudomonas aeruginosa LasR binding site

Abstract: Molecular docking methods were applied to simulate the coupling of a set of nineteen acyl homoserine lactone analogs into the binding site of the transcriptional receptor LasR. The best pose of each ligand was explored and a qualitative analysis of the possible interactions present in the complex was performed. From the results of the protein-ligand complex analysis, it was found that residues Tyr-64 and Tyr-47 are involved in important interactions, which mainly determine the antagonistic activity of the AHL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 39 publications
0
7
0
2
Order By: Relevance
“…Recently Blackwell also revealed that the interactions between a ligand and Tyr56 and Ser129 in LasR are also important in determining whether a ligand acts as an antagonist or agonist since these residues bond to the carbonyl of the 3-oxo-C12-HSL ligand to position the lactone head group towards Tyr 60, which is a key residue. 45,47 Docking experiments [48][49][50] revealed that the docked poses of 3-oxo-C12-HSL and of the 3-aminooxazolidinone analog (1) are similar, with the exception of the orientation of the 3-oxo group (see Fig. 4).…”
Section: Resultsmentioning
confidence: 99%
“…Recently Blackwell also revealed that the interactions between a ligand and Tyr56 and Ser129 in LasR are also important in determining whether a ligand acts as an antagonist or agonist since these residues bond to the carbonyl of the 3-oxo-C12-HSL ligand to position the lactone head group towards Tyr 60, which is a key residue. 45,47 Docking experiments [48][49][50] revealed that the docked poses of 3-oxo-C12-HSL and of the 3-aminooxazolidinone analog (1) are similar, with the exception of the orientation of the 3-oxo group (see Fig. 4).…”
Section: Resultsmentioning
confidence: 99%
“…These dramatic activity switches are seemingly caused by relatively subtle changes in ligand structure; however, the molecular bases for these flips in activity are unclear. In fact, there is virtually no information about the molecular mechanisms by which any non-native AHL analog modulates LuxR-type receptors (Ahumedo et al, 2014; Chen et al, 2011). Elucidating the causes of receptor activation versus inhibition by AHL analogs would not only improve our understanding of the molecular foundations of AHL-based QS, but would also augment our ability to design more potent molecular probes to modulate this signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, an additional hydrogen bond with the Tyr70 residue is found for most carbamate/thiocarbamate analogues. The Tyr70 residue, which is a conserved residue in the LuxR proteins family (equivalent to Tyr64 in LasR [38]) is confirmed as particularly important for interactions with AHLs analogues. For nitro compounds 7 and 11, two additional hydrogen bonds involving the nitro group and the Lys178 residue have been identified ( Figure 3B).…”
Section: Docking Studiesmentioning
confidence: 85%